Effect of glucocorticoids on nasal polyposis, with detection of inflammatory response by measurement of nitric oxide levels in nasal polyp tissue - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2013)
Objective: To investigate endoscopic staging, and nitric oxide levels in the polyp tissue, in patients with nasal polyposis undergoing glucocorticoid therapy. Methods: Nasal polyposis was evaluated using endoscopic staging and measurement of polyp tissue nitric oxide levels (chemiluminescence method). Forty-five nasal polyposis patients received either nasal therapy (n = 15), oral therapy (n = 15) or combined therapy (n = 15). Pre-treatment and post-treatment staging and nitric oxide levels were evaluated. Results: Endoscopic grading indicated significant post-treatment staging improvements in the oral (p = 0.016) and combined (p = 0.016) groups. Post-treatment staging differed significantly between the three groups (p = 0.041), with greater improvements in the oral and combined groups. All groups showed significantly lower post-treatment nitric oxide levels, compared with baseline, but post-treatment levels did not differ significantly between groups. A significant association was found between treatment response and nitric oxide level alteration. Conclusion: This study demonstrates the favourable effects of glucocorticoids on nasal polyposis, and alteration in nitric oxide tissue levels post-treatment. Nitric oxide level in nasal polyp tissue could be an indicator of treatment response, and may aid surgical decision-making by detecting cases that probably will not respond to medical treatment.
Keywords: Nasal Polyps; Nitric Oxide; Glucocorticoids; Corticosteroids; Chemiluminescence; STEROID TREATMENT; EXPRESSION; SYNTHASE; RHINOSINUSITIS